KEEFEKTIFAN MODEL PEMBELAJARAN SNOWBALL THROWING DENGAN PENDEKATAN KONTEKSTUAL TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS VIII MATERI BANGUN RUANG SISI DATAR - Ahmad Zaeni; Dwi Sulistyaningsih; Iswahyudi Joko Suprayitno (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
This study aims to determine the effectiveness of Snowball Throwing learning modelwith a contextual approach to the ability of mathematical communication. Thisresearch is an experimental research with population of all class VIII in MTsHidayatussibyan Lancar. Sampling technique using Saturated Sampling. Samplingtechnique using Saturation Sampling technique. The sample in this research is class VIII A, VIII B and class VIII C. Data collection method used in this research is interview, documentation, observation, questionnaire, and test. The results of this study show that learning achieves individual mastery with an average of 81.2 and classical completeness of 80.9%. The result of influence test showed the influence of student's activeness and interest toward the mathematical communication ability of 92%. Different test results also show that there is a difference of average mathematical communication ability between experimental class and control class, with the average of experimental class 81,2 while control class average is 77,2. Based on this it can be concluded that learning using Snowball Throwing model with a contextual approach to the ability of effective mathematical communication.Keywords: Snowball Throwing, contextual, mathematical communication ability.